2022
DOI: 10.1088/1674-1056/ac685f
|View full text |Cite
|
Sign up to set email alerts
|

Defect physics of the quasi-two-dimensional photovoltaic semiconductor GeSe

Abstract: GeSe has recently emerged as a photovoltaic absorber material due to its attractive optical and electrical properties as well as earth abundancy and low toxicity. However, the efficiency of GeSe thin-film solar cells (TFSCs) is still low compared to the Shockley-Queisser limit. Point defects are believed to play important roles in the electrical and optical properties of GeSe thin films. Here, we perform first-principles calculations to study the defect characteristics of GeSe. Our results demonstrate that no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…In contrast, Chen et al demonstrated that Se Ge is a neutral defect. 56 The difference in the calculation results about Se Ge is mainly due to the different formulas and parameter settings selected during the theoretical calculation. Their calculation results for other defects are consistent.…”
Section: Defect Properties In Q1d 2d and 3d Semiconductorsmentioning
confidence: 99%
“…In contrast, Chen et al demonstrated that Se Ge is a neutral defect. 56 The difference in the calculation results about Se Ge is mainly due to the different formulas and parameter settings selected during the theoretical calculation. Their calculation results for other defects are consistent.…”
Section: Defect Properties In Q1d 2d and 3d Semiconductorsmentioning
confidence: 99%